1620 Emergency Analgesia Administration in Children: Retrospective Analysis and Recommendations. (October 2012) - Hamdan, A; Thompson, M
Abstract : Introduction: Emergency analgesia administration in children is inadequate and guideline is insufficient. We aimed to analyse our department's paediatric pain management to inform and recommend necessary alterations to current practice. Methods: 800 children (0–16 years old) presenting with painful conditions to Queen Elizabeth Hospital Emergency Department within a 40-month period (01/01/2008–28/02/2012) were randomly identified from a prospective audit database and allocated into four groups according to pain scores (no, mild, moderate and severe pain; 200 children in each group). Analgesia types and differential diagnoses were recorded. Results: 56.9% children were males and mean age was 7.4 years. Of the ten main differential diagnoses, burn and long bone fractures frequently caused severe pain (80.8% and 50.9% respectively). 152 (25%) children with pain did not receive analgesia (39% of children with mild pain, 22% moderate pain and 15% severe pain; P=0.0001). For children with severe pain, 66.0% received simple analgesia (P=0.001) and only 38.5% received opioids (P=0.0001) with younger children (0–5 years old) receiving less intravenous diamorphine and more oral morphine than older children (13–18)(14% vs 52% and 46.0% vs 30.0% respectively; both P=0.0001). None was given intranasal diamorphine. Conclusions: Children with pain were not adequately analgised, especially those with severe pain and those that were younger. Children coming with conditions known to be severely painful (i.e. burn and long-bone fractures) should be considered for opioids regardless of their pain scores and opioid of choice is intranasal diamorphine, requiring no intravenous access with similar efficacy as the more common intravenous morphine.